Frequency and management of non pain symptoms, in cancer patients receiving palliative care: a prospective, observational and cross-sectional study in a tertiary care institute - Kichloo, Asra; Choudhary, Shabnam (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Cancer is the second most common cause of death caused by non-communicable diseases around the world, causing serious stress in both patients and caregivers including physical, psychological, social, and economic problems. Advanced cancer patients often experience a range of debilitating non-pain symptoms that significantly impact their quality of life. These symptoms can be due to the disease itself or the side effects of treatment. Effective management of these symptoms is crucial for palliative care (PC). The main aim of this study was to identify the frequency and management strategies of common non-pain symptoms in patients with cancer admitted to the oncology ward and inpatient PC patients, receiving PC. Methods: A prospective, observational study was conducted involving 100 patients, admitted to the oncology ward and inpatient PC patients, receiving PC. Structured interviews and questionnaires were used to collect data on non-pain symptoms experienced. The frequency of symptoms was analyzed using specific statistical methods and the effectiveness of various management approaches was evaluated. Results: The majority of the admitted patients were poly-symptomatic. The two most prevalent non-pain symptoms reported were lack of appetite (52%) and fatigue (51%) followed by nausea and vomiting, insomnia, constipation, shortness of breath, and anxiety. Ondansetron is the most common antiemetic and hydrocortisone is the most common steroid prescribed in the study population. Conclusions: In the findings of our survey significant prevalence of non-pain symptoms among cancer patients was seen, with fairly controlled symptoms after the management. This emphasizes the need for a comprehensive assessment of symptoms and routine monitoring of symptom management strategies in cancer patients.